International relations theory and the consequences of unipolarity - Ikenberry, G. John; Mastanduno, Michael; Wohlforth, William Curti , 1959- (Cambridge : Cambridge University Press, 2011)
"John ikenberry, Michael Mastanduno, and William C. Wohlforth American primacy in the global distribution of capabilities is one of the most salient features of the contemporary international system. The end of the Cold War did not return the world to multipolarity. Instead the United States - already materially preeminent - became more so. We currently live in a one superpower world, a circumstance unprecedented in the modern era. No other great power has enjoyed such advantages in material capabilities - military, economic, technological, and geographical. Other states rival the United States in one area or another, but the multifaceted character of American power places it in a category of its own. The sudden collapse of the Soviet Union and its empire, slower economic growth in Japan and Western Europe during the 1990s, and America's outsized military spending have all enhanced these disparities. While in most historical eras the distribution of capabilities among major states has tended to be multipolar or bipolar - with several major states of roughly equal size and capability - the United States emerged from the 1990s as an unrivaled global power. It became a "unipolar" state. Not surprisingly, this extraordinary imbalance has triggered global debate. Governments, including that of the United States, are struggling to respond to this peculiar international environment"-- Provided by publisher
"The end of the Cold War and subsequent dissolution of the Soviet Union resulted in a new unipolar international system that presented fresh challenges to international relations theory. Since the Enlightenment, scholars have speculated that patterns of cooperation and conflict might be systematically related to the manner in which power is distributed among states. Most of what we know about this relationship , however, is based on European experiences between the seventeenth and twentieth centuries, when five or more powerful states dominated international relations,and the latter twentieth century, when two superpowers did so. Building on a highly successful special issue of the leading journal World Politics, this book seeks to determine whether what we think we know about power and patterns of state behaviour applies to the current 'unipolar' setting and, if not, how core theoretical propositions about interstate interactions need to be revised"-- Provided by publisher
1. Introduction : unipolarity, state behavior, and systemic consequences -- 2. Unipolarity, status competition, and great power war -- 3. Legitimacy, hypocrisy, and the social structure of unipolarity : why being a unipole isn't all it's cracked up to be -- 4. Alliances in a unipolar world -- 5. System maker and privilege taker : US power and the international political economy -- 6. Free hand abroad, divide and rule at home -- 7. The liberal sources of American unipolarity -- 8. Unipolarity : a structural perspective -- 9. Unipolarity and nuclear weapons -- 10. From unipolarity to multipolarity : transition in sight? -- 11. Sell unipolarity? The future of an overvalued concept
Includes bibliographical references index
Keywords: Balance of power; International relations; International relations -- Philosophy; Unipolarity (International relations); World politics -- 1989-; United States -- Foreign relations -- 1989-